(3JQcjH GdCOhjI HMSH CLfGSgGs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS(B: (3CQjO Cf CPcQgG gfG GdCOhjI GdcKjQI GdefGaY hgj GdCOhjI GdJi JUdM dYdGL Ydd cKjQI , hef gPg GdCOhjI COhjI cKjQI djS EfeG jfJaY HgG ai GdYdd GdeNJdaI ? s
(3BNQgG (B:s
(3BNQ ef GdCOhjI GdJi jbGd dgG GdeHhdI GdeZjQ dJQcH GdHOf , JfaY ef hLY GdhQc hhLY GdeaGUd hGdaGdL hjbdY GdYdd GdJi bO WGd ecKgG , hjfJaY CjVkG ef GdUOGY s
(3GdebGdI GdNGeSIs
(3hGdSGOSIs
(3hGdSGHYIs
(3hYdi ghGeTgG HYV GdJUMjMGJ s
(3GdfSNI HgG MhGT s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs